Environmental study of gold mining tailings in the Ponce Enriquez mining area (Ecuador) (2016)
As a result of the artisanal mining activities in Ecuador (specially in Ponce Enriquez mining area, province of Azuay), great quantities of mining wastes have been disposed, usually without adequate management standards. Consequent acid rock drainage has been responsible of surface and underground water and surface water bodies. The aim of this study is to show a methodology which can characterize mining wastes to assist the taking decision process about remediation and/or ultimate disposition possibilities.